2017
DOI: 10.1038/s41598-017-06757-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA methylation in human cells using engineered dCas9-methyltransferases

Abstract: Mammalian genomes exhibit complex patterns of gene expression regulated, in part, by DNA methylation. The advent of engineered DNA methyltransferases (MTases) to target DNA methylation to specific sites in the genome will accelerate many areas of biological research. However, targeted MTases require clear design rules to direct site-specific DNA methylation and minimize the unintended effects of off-target DNA methylation. Here we report a targeted MTase composed of an artificially split CpG MTase (sMTase) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 53 publications
4
93
0
Order By: Relevance
“…More recently several groups have engineered dCas9 fused to the catalytic domain of distinct DNMTs to methylate CpG islands, CTCF binding sites, and promoter and enhancer regions in cancer cell lines, ESCs and primary cells (Liu et al, 2016; McDonald et al, 2016; Vojta et al, 2016; Lei et al, 2017; Xiong et al, 2017) (Fig. 1C).…”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…More recently several groups have engineered dCas9 fused to the catalytic domain of distinct DNMTs to methylate CpG islands, CTCF binding sites, and promoter and enhancer regions in cancer cell lines, ESCs and primary cells (Liu et al, 2016; McDonald et al, 2016; Vojta et al, 2016; Lei et al, 2017; Xiong et al, 2017) (Fig. 1C).…”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…Finally, an important limitation of our approach is the effectively low efficiency of methylation. This study showed much lower methylation rates (<1%) as compared to the dCas9methyltransferase fusion protein approach (30-70%) (Liu et al 2016;Amabile et al 2016;Vojta et al 2016;McDonald et al 2016;Stepper et al 2017;Lei et al 2017;Xiong et al 2017). This is due to a combination of factors, including the low transfection efficiency and rate of NHEJ of the Hap1 cell line, the lower integration rate of methylated DNA, and the availability of alternative outcomes that are also selected for, e.g.…”
Section: Discussionmentioning
confidence: 81%
“…For targeted methylation, this CRISPR/NHEJ approach represents an alternative to the previously demonstrated dCas9-methyltransferase domain fusion protein approach (Liu et al 2016;Amabile et al 2016;Vojta et al 2016;McDonald et al 2016;Stepper et al 2017;Lei et al 2017;Xiong et al 2017). While both approaches can produce targeted, scarless methylation of genomic DNA, the CRISPR/NHEJ approach is distinguished by the potential to program precisely which subsets of CpG dinucleotides are methylated, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using a split methyltransferase fused to dCas9 exhibited high specificity to target sites and suggested that the strategy limited off-target effects [53]. Although not yet attached to a targeting scaffold, TET2 has also been split and placed under the control of a small molecule modulator: Two inactive fragments were individually fused with either FKBP12 or FRB, and upon the addition of rapamycin, TET2 reassembled into a functional enzyme [54].…”
Section: Spatiotemporal Targeting Controlmentioning
confidence: 99%